PENGARUH LEARNING AGILITY TERHADAP KINERJA KARYAWAN PADA OTORITAS JASA KEUANGAN REGIONAL 6 SULAWESI MALUKU DAN PAPUA - Adinda Tasya Salsabila; Megawaty Megawaty (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to analyze and determine the effect of people agility, results agility, mental agility, and change agility on employee performance at the Regional Financial Services Authority offices 6th Sulawesi, Maluku and Papua. The research method used in this study is multiple linear regression with a sample of 40 respondents who are organic employees at the OJK Regional 6th Sulampua office. Data was collected by distributing questionnaires containing statements about learning agility. The results of the study partially show that people agility, results agility, mental agility, and change agility each have a positive and significant effect on employee performance. The results of the study simultaneously show that people agility, agility results, mental agility, and change agility have a positive and significant effect on employee performance.